Surgical Results of Endoscopic Endonasal Transsphenoidal Surgery for Pituitary Adenoma with Special Focus on Complication Rate - Amir, Sohail; Noman, Muhammad Ali; Ayub, Shahid (Journal of Liaquat University of Medical & Health Sciences, 2022)
Objective: To assess the results of endoscopic transsphenoidal surgery for pituitary adenoma with a particular focus on complication rate. Methodology: This retrospective descriptive case series of 45 consecutive patient studies included from the Neurosurgery unit, Hayatabad Medical Complex/MTI/ Peshawar, from August 2019 to July 2021. Patients of any age or gender who needed surgical removal of pituitary tumors were included. All non-pituitary lesions were excluded, including fungal lesions, angiofibroma, CSF rhinorrhea, craniopharyngiomas, and those managed conservatively. Pituitary adenomas were detected through MRI and biopsies from 45 patients with tumors. The outcome of the surgery, as well as any complications, were recorded. Data on demographic variables, the duration in the hospital, postoperative complications, and morbidity/mortality were collected. The data were analyzed with SPSS version 25. Results: There were 55.5% male and 44% female patients out of 45 cases. The average age was 42 years and five months. The most prevalent presenting complaint was headache (91%). The surgical outcome was good in microadenomas and macroadenomas (83% vs 65 %). In total, 76% of patients experienced early surgical symptom relief. Seventy-six percent of our patients reported immediate symptom reduction following surgery. CSF rhinorrhea 5(11%) was the most common complication. In 50% of the patients, a gross total resection was achieved. Conclusion: Pituitary adenomas are treated by endoscopic endonasal transsphenoidal surgery, which had an acceptable postoperative consequence. Keywords: Endoscopic Endonasal Transsphenoidal Surgery, Pituitary Adenoma, Complication